2020
DOI: 10.3390/cells9112473
|View full text |Cite
|
Sign up to set email alerts
|

Targeting AnxA1/Formyl Peptide Receptor 2 Pathway Affords Protection against Pathological Thrombo-Inflammation

Abstract: Stroke is a leading cause of death and disability globally and is associated with a number of co-morbidities including sepsis and sickle cell disease (SCD). Despite thrombo-inflammation underlying these co-morbidities, its pathogenesis remains complicated and drug discovery programs aimed at reducing and resolving the detrimental effects remain a major therapeutic challenge. The objective of this study was to assess whether the anti-inflammatory pro-resolving protein Annexin A1 (AnxA1) was able to reduce infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 70 publications
0
26
0
Order By: Relevance
“…These mediators act on different stages of the inflammatory cascade, restoring physiological responses by, for example, reducing neutrophil recruitment, inhibiting cytokine release, promoting apoptosis and phagocytosis, decreasing vascular permeability, regulating neutrophil‐platelet complexes, and delaying the overall cerebral thrombotic responses 7,8,57,107,108 . More specifically, in our study models, we have shown that Annexin A1 (and its N‐terminal–derived peptide) modifies neutrophil‐platelet interaction by activating the Annexin A1/FPR‐2 pathway in both neutrophils and platelets, with AnxA1 administration leading to reduced platelet activation and aggregate formation, delayed thrombosis, and enhanced platelet phagocytosis by neutrophils 7,106 . Some of these mechanisms were dependent upon AKT, intracellular Ca 2+ , and Rap1 and suggested a role for Annexin A1 to affect integrin ( α IIb β 3 ) activation 7 .…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…These mediators act on different stages of the inflammatory cascade, restoring physiological responses by, for example, reducing neutrophil recruitment, inhibiting cytokine release, promoting apoptosis and phagocytosis, decreasing vascular permeability, regulating neutrophil‐platelet complexes, and delaying the overall cerebral thrombotic responses 7,8,57,107,108 . More specifically, in our study models, we have shown that Annexin A1 (and its N‐terminal–derived peptide) modifies neutrophil‐platelet interaction by activating the Annexin A1/FPR‐2 pathway in both neutrophils and platelets, with AnxA1 administration leading to reduced platelet activation and aggregate formation, delayed thrombosis, and enhanced platelet phagocytosis by neutrophils 7,106 . Some of these mechanisms were dependent upon AKT, intracellular Ca 2+ , and Rap1 and suggested a role for Annexin A1 to affect integrin ( α IIb β 3 ) activation 7 .…”
Section: Introductionmentioning
confidence: 62%
“…(and its N-terminal-derived peptide) modifies neutrophil-platelet interaction by activating the Annexin A1/FPR-2 pathway in both neutrophils and platelets, with AnxA1 administration leading to reduced platelet activation and aggregate formation, delayed thrombosis, and enhanced platelet phagocytosis by neutrophils. 7,106 Some of these mechanisms were dependent upon AKT, intracellular Ca 2+ , and Rap1 and suggested a role for Annexin A1 to affect integrin (α IIb β 3 ) activation. 7 In addition, we also showed that aspirin-triggered lipoxin, a specific FPR-2, markedly attenuated inflammatory responses, including neutrophil-platelet aggregates in a murine model of ischemic stroke.…”
Section: Targeting Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…They identify the importance of this process and demonstrate the role of this process in facilitating embryo implantation in the uterus at the blastocyst stage. Vital et al [11] examined another aspect of FPR-AnxA1-its involvement in thrombus-induced inflammation during sepsis and sickle cell disease. Using intravital imaging together with an AnxA1 mimetic peptide, they observe that targeting this signaling through the Fpr2/ALX receptor helps reduce the severity of the inflammatory response.…”
Section: Role Of Annexins In Health and Diseasementioning
confidence: 99%
“…In fact, ANXA1 and its N-terminal peptides (Ac 2-26 and Ac 9-25 ) are endogenous anti-inflammatory and proresolving mediators, known to have significant effects in resolving inflammation in a variety of disease models and showing therapeutic potential in IRI [ 33 ]. ANXA1 has also protective role in myocardial infarction (MI) and stroke [ 34 ]. SAA is a sensitive marker of an acute inflammatory state [ 35 ] and although it is mainly associated with amyloidosis, it is involved in early atherogenic processes [ 36 ] and represents a marker of cardiovascular events [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%